2021
DOI: 10.1111/jch.14257
|View full text |Cite
|
Sign up to set email alerts
|

The association of hypertensive disorders of pregnancy with small for gestational age and intertwin birthweight discordance

Abstract: Available evidence shows conflicting results regarding the association between hypertensive disorders of pregnancy (HDPs)/preeclampsia (PE) and small for gestational age (SGA) and birthweight discordance (BWD). This retrospective study of 2131 twin pregnancies aimed to evaluate the association of HDPs/PE with the presence of SGA and BWD. The eligible pregnancies were categorized into four study groups: concordant pairs without SGA fetuses, discordant pairs without SGA fetuses, concordant pairs with SGA fetuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…On the other hand, growth discordance is associated with a high risk for preeclampsia in dichorionic twin pregnancy [ 15 , 34 ]. Sharing the same pathophysiologic mechanism may explain the interaction between preeclampsia and growth discordance.. Placental ischemia/hypoxia, which coexist either in preeclampsia or growth discordance women, appears to be responsible for this association [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, growth discordance is associated with a high risk for preeclampsia in dichorionic twin pregnancy [ 15 , 34 ]. Sharing the same pathophysiologic mechanism may explain the interaction between preeclampsia and growth discordance.. Placental ischemia/hypoxia, which coexist either in preeclampsia or growth discordance women, appears to be responsible for this association [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qiao et al 25 retrospectively analyzed 2122 women with twin pregnancies, drawing a conclusion that growth discordance is associated with a dose–response increased risk for PE in DC but not in MC twin pregnancy. Lin et al 26 studies have shown that SGA is associated with the development of HDP/PE, while discordant growth is associated with the severity of PE. Hiersch et al 14 included 1059 twin pregnancy women who was classified into one of four predetermined patterns based on the timing of onset and the progression of discordance: pattern 1, no significant discordance group (referent); pattern 2, early (<24 weeks' gestation) progressive discordance group; pattern 3, early discordance with plateau group; or pattern 4, late (≥24 weeks' gestation) discordance group, aiming to determine whether these patterns are predictive of adverse pregnancy outcomes, found that four distinct discordance growth patterns among twins that demonstrated a dose–response relationship with adverse outcomes include PTB and PE.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline information for all articles included in the review was shown in Table S2. Among all selected studies (one retrospective case-control study 31 and six retrospective cohort studies 22,23,[32][33][34][35] ), three were conducted in China, 31,34,35 two in the United States, 23,32 one in the UK, 33 and one in Italy. 22 All studies reported the incidence of SGA in twin pregnancies with hypertensive disorders and without.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…And the prevalence of SGA in all included articles ranged from 6.3% to 43.6%. Three studies [33][34][35] conducted stratification by twin chorionicity, one of them 34 cannot extract the original data. In addition, there was only one study 23 reported the results of dichorionic twin pregnancies.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation